Migraciones y sus consecuencias en la distribucin del espacio - Ferrer Lian, Sandra Judith (2022)
In this work of professional proficiency, I consider as a purpose that those students of second year of secondary education, achieve the objective of developing in the competence "Responsibly manage the space and the environment", through the development of explanations that have to do with the migrations. The problem presented in the session is the following: How do migrations influence the development of a country? The answer to the problem presented is developed in the learning session, within which teaching techniques and methods are also applied that are intertwined with the area of Social Sciences. Within the session, the following pedagogical methods are put into development: motivation, previous knowledge, cognitive conflict, etc. that go at the beginning of the session. When developing all this, the participation of the students and the respect between themselves must always be taken into account throughout the development of the session.